Cervical Cytological Findings among Women Attending a Tertiary Care Hospital in Sana'a, Yemen - Abdullah Abdu Al-Mikhlafy; Maha Abdulaziz; Amani Shamsher (University of Science and Technology, Sana'a, 2018)
Objective: To determine the frequency and pattern of abnormal cervical smear findings among women attending the University of Science and Technology Hospital (USTH) in Sana'a city. Methods: This study is a retrospective, cross-sectional study. Records of women examined by conventional Pap smears in the Histopathology Laboratory of USTH over a 4-year period (from January 2013 to December 2016) were retrieved and analyzed for abnormalities according to the Bethesda system. Results: Of 688 cases, 599 with satisfactory records were analyzed. The mean age of the cases was 39.1810.23 years (range: 1975). Epithelial cell abnormalities (ECAs) were found in 47 cases (7.8%), and these were categorized as follows: ASCUS in 4.5% (27/599) of cases followed by atypical glandular cells (AGC) (2.2%; 13/599) and LSIL (0.5%; 3/599), while ASCH and HSIL abnormalities were equally observed among 0.3% (2/599 each) of cases. Of patients positive Pap smear findings, ASCUS was the most frequent type of ECA (57.4%; 27/47) followed by AGC (27.7%; 13/47) and LSIL (6.4%; 3/47), while ASCH and HSIL were the least frequent ECAs among Yemeni patients. ECAs were significantly more prevalent among women aged >40 years (10.8%) compared with those aged <40 years (5.5%). Conclusions: Cervical cytological abnormalities are not uncommon among women in Yemen, where the AGC is frequent among about a third of women with abnormal Pap smear findings and affects women of different ages. This requires more attention and training of doctors to master good sample taking, preparation and diagnosis with a focus on glandular changes.